The museological unconscious : communal (post) modernism in Russia - Victor Tupitsyn. (MIT Press)
Contents: Civitas solis: ghetto as paradise -- Communal (post) modernism: a short history -- Moscow communal conceptualism -- Icons of iconoclasm -- The sun without a muzzle -- If I were a woman -- Pushmi-Pullyu: St. Petersburg-and-Moscow -- Batman and the Joker: the thermidor of the bodily -- Body-without-a-name -- Notes on the museological unconscious -- Negativity mon amour -- Post-autonomous art -- Rublevskoe Chaussé́́́́e.Includes bibliographical references and index.